Machine learning technique for energy efficiency analysis of HVAC systems - Ma, Biao (2014)
Energy usage in air-conditioning system accounts for approximately 50% of the total energy consumption in commercial building sector in Singapore, presenting a significant opportunity for minimizing the energy consumption improving the energy efficiency of its operation. Machine learning techniques have been introduced to facilitate the modeling and optimizing of HVAC system as they are able to handle nonlinear dynamic and complex data of HVAC system.